2019
DOI: 10.48550/arxiv.1909.07280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermodynamic extended phase space and $P-V$ criticality of black holes at Pure Lovelock gravity

Milko Estrada,
Rodrigo Aros

Abstract: In this work the chemistry of asymptotically AdS black hole, charged and uncharged, solutions of Pure Lovelock gravity is discussed. For this the mass parameter of black holes is identified with the enthalpy of the system together with the promotion of the cosmological constant to a thermodynamics variable proportional to the pressure of the system. The equations of state for both, charged and uncharged, are obtained. It is shown that the charged case behaves as a Van der Waals fluid. The existence of a first … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…[44] by using Hamiltonian formalism. Furthermore, the critical behavior of pure Lovelock black holes was explored [45]. It was shown that the critical exponents and the critical behavior of pure Lovelock black holes are the same as the van der Waals fluid (VdW).…”
Section: Introductionmentioning
confidence: 99%
“…[44] by using Hamiltonian formalism. Furthermore, the critical behavior of pure Lovelock black holes was explored [45]. It was shown that the critical exponents and the critical behavior of pure Lovelock black holes are the same as the van der Waals fluid (VdW).…”
Section: Introductionmentioning
confidence: 99%
“…[29]. Thermodynamic extended phase space and P − V criticality of the black holes in pure Lovelock gravity have been also probed [30]. Based on the advantages of the quasitopological gravity over the Lovelock theory as mentioned, now, we are willing to obtain the solutions of the pure quasitopological Yang-Mills black hole in the second part of this paper.…”
Section: Introductionmentioning
confidence: 99%